Performance Analysis of Single-Phase Uncontrolled Full-Wave Rectifier On Three-Phase AC Generator - John Vernando Purba; Anggara Trisna Nugraha; Muhammad Fikri Fathurrohman (Journal of Marine Electrical and Electronic Technology, 2023)
Rectifier circuits are fundamental in electrical engineering systems, serving as a critical component in converting alternating current (AC) generated by a three-phase AC generator into direct current (DC). The key component in these circuits is typically a diode. Rectifier systems can be classified into controlled and uncontrolled types. A single-phase uncontrolled full-wave rectifier, in particular, offers high output power by effectively converting the negative voltage of an AC signal into a positive voltage. This characteristic ensures a stable and efficient DC output for various applications. In circuits with an uncontrolled rectifier, the inclusion of a capacitor significantly enhances performance by acting as an active filter, minimizing ripple and ensuring that the output current approaches a pure DC waveform. This study employs a structured methodology encompassing system identification, analytical calculations, process flowchart development, simulation design, and experimental data measurement to comprehensively evaluate the performance of a full-wave single-phase uncontrolled rectifier in the context of a three-phase AC generator. The outcomes of this study highlight the operational characteristics of single-phase full-wave rectifier circuits under different load conditions and their effectiveness in improving power quality and stability. These findings contribute valuable insights into optimizing rectifier circuit design for power conversion systems.